Practice Patterns of Palliative Radiotherapy for Advanced Cancer at a Large Institute in Saudi Arabia - Wsam Ghandourh; Zaheeda Mulla; Belal Sharaf; Elham Ghabashi; Anan Bamakhrama (Palliative Medicine Reports)
Background and Aims: Palliative radiotherapy practice patterns have been reported to vary widely, with a notable underutilization of single fraction treatment schedules. This study aims to investigate the outcomes and care patterns among patients receiving palliative radiotherapy for advanced cancer at a high-volume institution in Saudi Arabia. Materials and Methods: Electronic records were used to identify patients receiving palliative radiotherapy for advanced cancer between 2018 and 2023. Univariate analyses were used to assess tumor and patient factors potentially associated with single fraction use, including primary tumor, target site, sex, age, admission status, and geographical remoteness from the center. Survival outcomes were analyzed using Kaplan–Meier curves. Results: A total of 792 patients receiving 990 radiotherapy courses were identified. 60% of patients were female and 40% were male. The median age was 56.5 years (16.4 standard deviation [SD]). The most common primary histology was breast (34%), followed by gastrointestinal (13%). Single fraction treatment schedule represented 28.7% of all treatments and were most commonly used for extremities (p < 0.05). Multiple-fraction treatment schedule was more likely to be used for breast, chest, head-and-neck, pelvis, and spine (p < 0.05). The median survival was 6.9 months (SD = 8.9 months) and 25% of patients died within 30 days following radiotherapy. Median survival was shorter for male gender, admitted patients and those who did not complete their course of treatment (log-rank p < 0.05). Conclusion: Single fraction radiotherapy is underutilized in the management of advanced cancer patients, particularly those with bone metastases. Further research is warranted to develop clinical decision-making tools that enhance adherence to clinical guidelines and optimize treatment outcomes.